Omental tuberculosis (TB) is a rare disease which can mimic Gastrointestinal malignancies: A case report. (2020) - Pragalathan, B.; Omar Mohamed Ozaal, A.M.; Lavanya, S.; Raviraj, S.
Highlights: Omental tuberculosis (TB) is a rare disease which can mimic Gastrointestinal malignancies. Histology is the confirmatory diagnostic tool. Medical management is the treatment of choice for omental TB. Surgery is needed when complications occur in extrapulmonary TB. Abstract: Introduction: Omental tuberculosis is a rare disease which can mimic Gastrointestinal malignancies. It should be considered as one of the differential diagnosis when the patient presents with abdominal mass with vague symptoms. Histological diagnosis is the final conclusion in these patients. Presentation of case: An elderly male patient who presented with epigastric pain with epigastric mass and diagnosed with omental tuberculosis as a result of USS guided tissue biopsy revealed granuloma with central caseous necrosis. The size of the mass completely resolved after completion of anti TB treatment in this patient. Discussion: Presence of caseous necrosis with granulomas in histology and positive culture of tuberculosis from tissue are the definitive diagnosis for omental tuberculosis. And the response to treatment with anti TB drug supports the diagnosis. Conclusion: Omental TB is a rare entity which can be misdiagnosed as GI malignancies. Medical management is the treatment of choice for omental TB. Surgery is needed when complications occur in extrapulmonary TB.